PERGESERAN BUDAYA MASYARAKAT BENGKULU DALAM TRANSFORMASI MOTIF HURUF ARAB BATIK BESUREK: BENGKULU COMMUNITY'S CULTURAL SHIFT IN THE TRANSFORMATION OF BESUREK BATIK ARABIC LETTER MOTIFS - Anggo Ahmad Saputra; Krishna Hutama; Yan Yan Sunarya (Universitas Trisakti, 2025)
The cultural shift of Bengkulu society in the transformation of Besurek batik arabic letter motifs. Besurek Batik is a Bengkulu cultural heritage that is rich in history and aesthetics. The uniqueness of this batik lies in the use of Arabic letter motifs, which reflect the acculturation of local culture with Islamic influences. This research aims to examine the cultural shift in Bengkulu society in the transformation of Arabic letter motifs on Besurek Batik. The method used is descriptive qualitative with a case study approach, through interviews and observation. The research results show that changes in Besurek Batik motifs reflect changes in the values and cultural identity of the people of Bengkulu, which are influenced by globalization, modernization and socio-economic changes. The Arabic letter motifs on Besurek Batik still maintain traditional values while adapting to contemporary trends, making Besurek Batik a medium that connects past and present, as well as local and global.